Defining motivation in video game‐based training: Exploring the differences between measures of motivation. (9th August 2021) - Sanchez, Diana R.; Nelson, Tristan; Kraiger, Kurt; Weiner, Erik; Lu, Yucheng; Schnall, Jasmine
Abstract: Game‐based training research has produced various definitions and measures for learner motivation. Inconsistent findings on learner motivation may have contributed to the misapplication of one type of motivation to explain another; inhibiting future research and generating false implications. This study compared 172 students in game‐based or computer‐based training learning French. Results showed unique relationships between three measures of learner motivation (i.e. motivation to learn, intrinsic motivation and engagement). Motivation to learn did not differ between conditions, while intrinsic motivation and engagement did. A significant portion of the variance in content reactions was explained by all three measures of motivation, while variance for technology reactions was explained only by the motivation to learn and engagement. None of the measures for motivation accounted for significant variance in declarative or procedural knowledge. Results indicate key differences in three measures of motivation.